The Relationship Between the Implementation of Islamic Values and Patient Loyalty in Inpatient Rooms - Alkhaidar, Arrum Arrifani; Qowi, Nurul Hikmatul; Ubudiyah, Masunatul (Universitas Airlangga, 2025)
Introduction: Patient loyalty represents a critical challenge for hospitals and other healthcare organizations. A low level of patient loyalty may negatively affect an institution’s competitiveness and reflect poorly on the quality of healthcare services and workforce performance. In increasingly diverse healthcare settings, incorporating values that align with patients’ beliefs and expectations may play a role in fostering satisfaction and loyalty. This study aims to analyze the relationship between implementing Islamic values in inpatient care and patient loyalty. Method: This study applied a correlational analytic design with a cross-sectional approach. Data were collected from a sample of 100 inpatients, selected through consecutive sampling over a two-week period. The study investigated the relationship between the implementation of Islamic values and patient loyalty. Two instruments were used to measure the study variables: the Islamic Service Questionnaire and the Patient Loyalty Questionnaire. Data were analyzed using the Spearman rank-order correlation test to determine the strength and direction of the association between the two variables. Results: A total of 66% of patients perceived the implementation of Islamic values by nurses to fall within the moderate category. Similarly, 70% of patients demonstrated a moderate level of loyalty. Statistical analysis using the Spearman rank-order correlation test showed a significant relationship between the implementation of Islamic values and patient loyalty (p = 0.009; rₛ = 0.260), indicating a positive, albeit weak, correlation between the two variables. Conclusion: This study demonstrates a significant positive relationship between the implementation of Islamic values in nursing care and patient loyalty in inpatient settings. By addressing spiritual needs, modifying the care environment to reflect Islamic principles, and providing adequate worship facilities, healthcare institutions may enhance the overall patient experience and increase retention. Future research is recommended to explore the long-term impact of faith-based care models on patient outcomes in broader and more diverse hospital settings.